2020
DOI: 10.1101/2020.07.24.20149815
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic evaluation and external validation of 22 prognostic models among hospitalised adults with COVID-19: An observational cohort study

Abstract: Background The number of proposed prognostic models for COVID-19, which aim to predict disease outcomes, is growing rapidly. It is not known whether any are suitable for widespread clinical implementation. We addressed this question by independent and systematic evaluation of their performance among hospitalised COVID-19 cases. Methods We conducted an observational cohort study to assess candidate prognostic models, identified through a living systematic review. We included consecutive adults admitted to a se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
75
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 41 publications
(20 reference statements)
7
75
0
2
Order By: Relevance
“…Moreover, the Authors found that (within their data) baseline oxygen saturation on room air was the most predictive variable for in-hospital worsening, while age was the most predictive variable for in-hospital mortality. Astonishingly, none of the 22 CPMs included in the external validation demonstrated significantly higher clinical utility when compared with these variables alone [4]. Together, these results imply that none of the selected CPMs should be recommended for adoption in daily clinical routine.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…Moreover, the Authors found that (within their data) baseline oxygen saturation on room air was the most predictive variable for in-hospital worsening, while age was the most predictive variable for in-hospital mortality. Astonishingly, none of the 22 CPMs included in the external validation demonstrated significantly higher clinical utility when compared with these variables alone [4]. Together, these results imply that none of the selected CPMs should be recommended for adoption in daily clinical routine.…”
mentioning
confidence: 89%
“…Some caution is required in the interpretation of the findings of Gupta et al [4]. First, this is a single site validation.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Note that the implementation of any new algorithm is likely to influence the data routinely collected, by assigning increased importance in those features that are used as model inputs, while generating new information (that is, the model outcomes), thus completing the development cycle, and initiating a new cycle. comment subsequent validation studies have found simple bedside measurements outperform many of these models 11 . It is likely that at least some research waste could be avoided by full and transparent reporting, which helps to avoid pursuing predictive models that are unlikely to reach clinical use.…”
Section: Assessment and Adoptionmentioning
confidence: 99%